MULTIPASS, a rice R2R3‐type MYB transcription factor, regulates adaptive growth by integrating multiple hormonal pathways. (26th August 2013) - Schmidt, Romy; Schippers, Jos H. M.; Mieulet, Delphine; Obata, Toshihiro; Fernie, Alisdair R.; Guiderdoni, Emmanuel; Mueller‐Roeber, Bernd
Summary Growth regulation is an important aspect of plant adaptation during environmental perturbations. Here, the role of MULTIPASS (OsMPS), an R2R3‐type MYB transcription factor of rice, was explored. OsMPS is induced by salt stress and expressed in vegetative and reproductive tissues. Over‐expression of OsMPS reduces growth under non‐stress conditions, while knockdown plants display increased biomass. OsMPS expression is induced by abscisic acid and cytokinin, but is repressed by auxin, gibberellin and brassinolide. Growth retardation caused by OsMPS over‐expression is partially restored by auxin application. Expression profiling revealed that OsMPS negatively regulates the expression of EXPANSIN (EXP) and cell‐wall biosynthesis as well as phytohormone signaling genes. Furthermore, the expression of OsMPS‐dependent genes is regulated by auxin, cytokinin and abscisic acid. Moreover, we show that OsMPS is a direct upstream regulator of OsEXPA4, OsEXPA8, OsEXPB2, OsEXPB3, OsEXPB6 and the endoglucanase genes OsGLU5 and OsGLU14. The multiple responses of OsMPS and its target genes to various hormones suggest an integrative function of OsMPS in the cross‐talk between phytohormones and the environment to regulate adaptive growth.